2020
DOI: 10.1007/s11696-020-01414-9
|View full text |Cite
|
Sign up to set email alerts
|

C3 amino-substituted chalcone derivative with selective adenosine rA1 receptor affinity in the micromolar range

Abstract: To identify novel adenosine receptor (AR) ligands based on the chalcone scaffold, herein the synthesis, characterization and in vitro and in silico evaluation of 33 chalcones ( 15 – 36 and 37 – 41 ) and structurally related compounds ( 42 – 47 ) are reported. These compounds were characterized by radioligand binding and GTP shift assays to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“…The structure, molecular mass and purity of these compounds were verified by hydrogen-1 / protium ( 1 H) and carbon-13 ( 13 C) nuclear magnetic resonance (NMR) spectra, mass spectroscopy and HPLC (see supplementary material). It should be noted that, protons on the NH 2 -group (e.g., 6l ) and the OH-group (e.g., 6k ) are not always visible on a 1 H NMR spectrum as protons attached to a N-atom (or O-atom) are acidic, and thus, exchangeable [ 50 ]. Halogen-carbon bonds tend to cause splitting of 13 C NMR chemical shifts (e.g., 6p and 7a ) due to deshielding by the F-atom on the directly bonded carbon nucleus [ 51 ] which results in multiple carbon peaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure, molecular mass and purity of these compounds were verified by hydrogen-1 / protium ( 1 H) and carbon-13 ( 13 C) nuclear magnetic resonance (NMR) spectra, mass spectroscopy and HPLC (see supplementary material). It should be noted that, protons on the NH 2 -group (e.g., 6l ) and the OH-group (e.g., 6k ) are not always visible on a 1 H NMR spectrum as protons attached to a N-atom (or O-atom) are acidic, and thus, exchangeable [ 50 ]. Halogen-carbon bonds tend to cause splitting of 13 C NMR chemical shifts (e.g., 6p and 7a ) due to deshielding by the F-atom on the directly bonded carbon nucleus [ 51 ] which results in multiple carbon peaks.…”
Section: Resultsmentioning
confidence: 99%
“…The potential interaction of compounds 6c , 6d , 6m , 6o , 6q and 7c with cytochromes P450 (CYP) isoenzymes was also evaluated. This is important for determination of drug-drug interactions and adverse effects due to low drug clearance leading to accumulation of the drug [ 50 , 51 ]. Generally, all the compounds are inhibitors of CYP isoforms (CYP1A2, CYP2C19, CYP2C9, CYP3A4) with a few exceptions, but they did not affect CYP2D6 except compound 6q .…”
Section: Resultsmentioning
confidence: 99%
“…A series of 27 amino-substituted chalcones was synthesised by van Rensburg et al [ 66 ] and the effect of the substituent (e.g., halogen) and the position of this substituent on the B ring of the chalcone on the affinity for the rat A 1 R (rat whole membranes) and rat A 2A R (rat striatal membranes) was investigated. The degree and type of binding affinity to these receptors was determined in a radioligand binding and a guanosine triphosphate (GTP) shift assays.…”
Section: Adenosine a 2a And A 1 ...mentioning
confidence: 99%
“…This compound had a low relative affinity for A 2A R rat (specific binding [ 3 H] NECA of 75% at 100 µM). Structure-activity relationship analysis showed that the amino group in the meta position of the A ring of chalcone and the bromine atom in the meta position of the B ring of chalcone played key roles in the affinity for A 1 R [66]. AR ligands have attracted increasing interest in drug design and development for the treatment of neurodegenerative diseases.…”
Section: Aniline-based Chalconesmentioning
confidence: 99%
“…Reaction intermediates (1 and 2) and lead compounds (3, 8 and 9) were synthesised using previously described methods (see Supplementary Material). Lead compounds 4-7 were obtained from a recent study where they were synthesised and reported (Janse van Rensburg et al, 2021).…”
Section: Chemistrymentioning
confidence: 99%